The importance of implementing courses of specialization as a second alternative to the current graduation process for obtaining the bachelor’s degree in English Teaching and the Bachelor’s degree in Modern languages: Specialization in French and English at the Foreign Language Department, University of El Salvador - Oliva Villalobos, Andrea María; Ramos Mónico, César Geovanny; Rosales Ramos, Flor Azucena (2024)
“Achieving the goals is a Heroic labor” by Ernie Larsen”. Getting graduated from a university is a dream that every student has, after working hard to approve the graduation process in superior studies to start working as a professional by putting into practice the knowledge learnt. In the Foreign Language Department of the University of El Salvador, there are more than 135 students who graduate every year; however, not all the students that start a major have the opportunity to get graduated due to many facts. There are some of them that have already approved all the subjects that are required in the career, but they have not got the bachelor degree yet since they have not completed the graduation process with the requirements needed. The most important requirement in the graduation process is to carry on a research paper that is aimed to study a specific problem affecting students from the Foreign Language Department (FLD) or any other topic relate to teaching-learning process of a foreign language in order to provide possible solutions that are supposed to be applied in the academic field. Nevertheless, most of the students think that this research extends the time to graduate because they have to go through a long process to complete this task that most likely in the end, it will not be taken into consideration by the authorities of the University of El Salvador. One of the main reasons why the researchers are proposing to have an update in the graduation process is for the students to be prepared for their labor life in a better way. This goal has been affected due to the lack of updates in the majors’ curricula at the FLD, which is causing to have a weak education in a constantly changing economy since nowadays it is important to be at the forefront of all new labor updates and requirements so that students are better prepared to face the challenges.